Istirātījiyyātu al-Nafādi Ilá al-Muʻjami al-Żihnī lada Talāmīżi al-Sanati al-Śāliśati min al-Taʻlīmi al-Śānawī al-Iʻdādiyyi [Mental Lexicon Access Strategies for Students of the Third Year of Preparatory Secondary Education] - Ghoura, Hamza; Bouanani, Mostafa (OKARA: Jurnal Bahasa dan Sastra, 2023)
Lexical units are organized within the mental lexicon, and the processes of constructing, processing, and accessing them are organized according to extremely complex mental pathways. This requires language speakers to activate them and use them quickly and effectively in their linguistic achievement. The more the speaker's access to his mental lexicon is sound, the more he can communicate successfully in different linguistic contexts. This research paper attempts to contribute to deriving some appropriate strategies for accessing the mental lexicon according to the parametric peculiarities of the Arabic language by linking these strategies to four basic criteria (the criterion of phonetic similarity, the criterion of spelling form, the criterion of semantic similarity, the criterion of grammatical predicate). This study was based on field research that targeted a sample of 40 students belonging to the third year of preparatory secondary education within a Moroccan public educational institution. The study used tests related to linguistic information that allows access to lexical units within the mental lexicon, aiming to analyze and measure them in the student's linguistic achievement. The results revealed that there is a strong influence of standards of access to the mental lexicon on the performance of learners in written expression and that there is a large gap between what is stipulated in educational documents and what students produce in their construction writings based on their level in this academic level.